Artisan iris-claw lenses for the correction of aphakia in children following lensectomy for ectopia lentis. Issue 3 (26th July 2011) - Cleary, Catherine; Lanigan, Bernadette; O'Keeffe, Michael
Abstract : Purpose: To describe the results of Artisan iris-claw lens implants in children with aphakia following lensectomy for ectopia lentis. Method: We measured visual acuity, refractive error and endothelial cell counts and recorded complications in a group of children after insertion of Artisan iris-claw implants. Results: Artisan implants were implanted in eight eyes of five children. Mean follow-up was 28 months (range: 4–58 months). The mean preoperative LogMAR best-corrected visual acuity was 0.21±0.2, and postoperatively, mean LogMAR uncorrected visual acuity was 0.04±0.09 (p=0.04). Mean endothelial cell count was 3312±277 cells preoperatively and 2913±268 cells postoperatively, representing a mean cell loss of 14.2% (p<0.001). Mean defocus equivalent was 11.38±1.04 preoperatively and 2.34±0.66 postoperatively. We encountered no postoperative complications in any of the eyes. Conclusion: Artisan iris-claw implants are safe and effective in the correction of aphakia in children following lensectomy for ectopia lentis, enabling good spectacle-free distance vision in 75% of eyes with no postoperative complications.